2013
DOI: 10.1186/1477-7525-11-160
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth, posttraumatic stress and psychological adjustment in the aftermath of the 2011 Oslo bombing attack

Abstract: BackgroundExperiencing potentially traumatic events is associated with psychological distress. However, some survivors also experience positive personal and psychological changes in the aftermath of trauma.MethodsThe present study investigated perceived posttraumatic growth in 197 ministerial employees who were present at work during the 2011 Oslo bombing attack. The relationships between trauma-exposure, peritraumatic reactions and posttraumatic growth were studied. Moreover, the adaptive significance of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
1
30
0
2
Order By: Relevance
“…Foreign translations . Several articles using foreign translations of the PCL‐S were located in the literature, accompanied by various diverse psychometric evidence, including two in Norwegian (Blix, Bang Hansen, Skogbrott Birkeland, Nissen, & Heir, ; Hem, Hussain, Wentzel‐Larsen, & Heir, ), two in French (Dubosc et al, ; Ventureyra, Yao, Cottraux, Note, & De Mey‐Guillard, ), and three in Chinese (Erbes, Meis, Polusny, & Compton, ; Jenkins, Belanger, Connally, Boals, & Durón, ; L. Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Foreign translations . Several articles using foreign translations of the PCL‐S were located in the literature, accompanied by various diverse psychometric evidence, including two in Norwegian (Blix, Bang Hansen, Skogbrott Birkeland, Nissen, & Heir, ; Hem, Hussain, Wentzel‐Larsen, & Heir, ), two in French (Dubosc et al, ; Ventureyra, Yao, Cottraux, Note, & De Mey‐Guillard, ), and three in Chinese (Erbes, Meis, Polusny, & Compton, ; Jenkins, Belanger, Connally, Boals, & Durón, ; L. Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to another recent study in living kidney and liver donors, 67 our sample reported average levels of personal psychological growth from the experience comparable to those in populations exposed to other psychologically and/or physically stressful events. 6873 They were equally or more likely than other types of donors to feel that they were “better persons” for having donated. 74–76 …”
Section: Discussionmentioning
confidence: 99%
“…Det er forsket på personlig vekst som resultat av å løse krevende nye utfordringer og oppgaver i forbindelse med en traumatisk hendelse (8,9). Slik vekst blir ofte kalt posttraumatisk vekst (8).…”
Section: Sammendragunclassified
“…Slik vekst blir ofte kalt posttraumatisk vekst (8). Undersøkelser av psykososialt personell som skal bistå mennesker i kriser, viser også personlig vekst (10).…”
Section: Sammendragunclassified